2017
DOI: 10.18632/oncotarget.23290
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive transcriptional landscape of porcine cardiac and skeletal muscles reveals differences of aging

Abstract: Aging significantly affects the cardiac muscle (CM) and skeletal muscles (SM). Since the aging process of CM and SM may be different, high throughput RNA sequencing was performed using CM and SM in different age conditions to evaluate the expression profiles of messenger RNA (mRNA), long non-coding RNA (lncRNA), micro RNA (miRNA), and circular (circRNA). Several mRNAs, lncRNAs, and miRNAs were highly expressed and consistently appeared in both ages in one of the two muscle tissues. Gene ontology (GO) annotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 77 publications
1
35
0
1
Order By: Relevance
“…In pigs, recent work has demonstrated circRNAs' involvement in various organismal processes. For example, through a comprehensive analysis of porcine cardiac and skeletal muscles, Chen et al (2018) showed that circRNAs contribute to differences in aging. Moreover, circRNAs were defined as a new biomarker in metabolism-related diseases based on a study of circRNAs occurring in the subcutaneous adipose tissues of two pig breeds (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In pigs, recent work has demonstrated circRNAs' involvement in various organismal processes. For example, through a comprehensive analysis of porcine cardiac and skeletal muscles, Chen et al (2018) showed that circRNAs contribute to differences in aging. Moreover, circRNAs were defined as a new biomarker in metabolism-related diseases based on a study of circRNAs occurring in the subcutaneous adipose tissues of two pig breeds (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding and slaughtering standards of the pigs were performed as described in previous literature (Chen et al, 2018). As in previous research, piglet weaning was executed at the age of ± days.…”
Section: Animalsmentioning
confidence: 99%
“…Pigs were not allowed to access food one night before slaughtering and had a resting period of 2 h after transportation. To exsanguinate and relief the pain, a sudden electric shock of 90 V and 50 Hz for 10 s was administered (Chen et al, 2018).…”
Section: Animalsmentioning
confidence: 99%
“…Cardiac senescence accompanies ageing and may decrease heart function. Chen et al (2018) reported that aging significantly affects the cardiac muscle. By using high throughput RNA sequencing, they found up-regulated circRNAs and 1 down-regulated gene in cardiac muscle during aging.…”
Section: Cardiac Senescencementioning
confidence: 99%